Editors’ Word - Ejdus, Filip; Kovačević, Marko; Vujinović, Nikola (Journal of Regional Security, 2018)
The Journal of Regional Security has a great pleasure to welcome Amitav Acharya, Andrew Grant, Hilde Haug, and Rok Zupančič as the new members of its Editorial Board. In 2014, with their help we aim to continue to develop the Journal by publishing cutting edge research in the field of regional security studies. Next year we will particularly be interested in Regional Security Complex Theory (RSCT). Over the course of the past decade there has been a growing interest in regional security studies particularly thanks to the work done by Barry Buzan and Ole Wæver. Their influential work Regions and Powers: The Structure of International Security published in 2003 represents the most authoritative account of the RSCT to date. Over the years, their book informed a great number of theoretical and empirical discussions. Ten years on, it is time to take stock of the scope and perspectives of the debate generated by this book.